Risk management of cytotoxic drug contamination: Evaluation of the securing of the cytotoxic preparation circuit at Ibn Sina Hospital-CHU Rabat - DAOUDI, Hajar; JAMAI-NAFIA, Hanane; EL HARTI, Jaouad; BOUSLIMAN, Yassir; SERRAGUI, Samira; AIT EL CADI, Mina (Jour Med Resh and Health Sci, 2023)
Introduction: The cytotoxic drug circuit is a complex process involving numerous healthcare professionals and implementing protective measures. The objective of this study is to control the circuit of cytotoxic drugs and evaluate the risk of contamination to the staff, patients, and environment in order to implement corrective measures to mitigate the risk. Materials & Methods: We chose the Failure Mode and Effects Analysis (FMEA) method to identify failure modes and estimate the risks associated with the occurrence of these failures, in order to initiate necessary corrective or preventive actions. We selected quinine sulphate as the tracer drug, which has the advantage of being colorless after reconstitution and fluorescent under UV light. We transferred it from the ampoule to a sterile vial to adapt it to closed-system preparation. Results & Discussions: Simulating the spread of contamination in the chemotherapy circuit using quinine helped identify critical points at risk of contamination in several areas, with a predetermined level of criticality indicated by a Risk Priority Index (RPI) ranging from 9 to 16. The areas with an RPI of 12 included the dispensing room, isolator gloves (16), transport cooler for preparations (9), nursing unit (nurse's gloves (11), patient's bed (9), and workbench (10)), and waste disposal (9). The remaining areas posed a low level of risk. Consequently, we established corrective measures by improving handling techniques for all involved parties, including preparers, nurses, and pharmacists, to minimize cytotoxic projection in accordance with proper preparation and administration practices. Conclusion: This risk analysis allowed for the establishment of specific measures aimed at optimizing each failure, thereby protecting staff, patients, and the environment from the risks associated with cytotoxic drugs.